Why Are Women Predisposed to Intracranial Aneurysm? - Fréneau, Milène; Baron-Menguy, Céline; Vion, Anne-Clémence; Loirand, Gervaise (Frontiers in Cardiovascular Medicine, 2022)
Intracranial aneurysm (IA) is a frequent and generally asymptomatic cerebrovascular abnormality characterized as a localized dilation and wall thinning of intracranial arteries that preferentially arises at the arterial bifurcations of the circle of Willis. The devastating complication of IA is its rupture, resulting in subarachnoid hemorrhage that can lead to severe disability and death. IA affects about 3% of the general population with an average age for detection or rupture around 50 years. IAs, whether ruptured or unruptured, are more common in women than in men by about 60% overall, and more especially after the menopause where the risk is double compare to men. Although these data support a protective role of estrogen, differences in the location and number of IAs observed in women and men under the age of 50 suggest that other underlying mechanisms participate to the greater IA prevalence in women. The aim of this review is to provide a comprehensive overview of the current data from both clinical and basic research, and a synthesis of the proposed mechanisms that may explain why women are more prone to develop IA.